(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
By working on texts on various topics in the textbooks of primary classes, it is appropriate to closely connect them with spiritual-moral, literary-aesthetic education. Particular attention is paid to the variety of genres, poetic perfection, and the suitability of the students’ knowledge level and age characteristics of the texts selected for each topic in the textbooks. It is one of the important tasks of teachers to make students understand that the knowledge, skills and abilities acquired with the help of textbooks will be necessary in the future life.